-32y-2=13y-56

Combine y and 32.

-y⋅32-2=13y-56

Move 3 to the left of y.

-3y2-2=13y-56

-3y2-2=13y-56

Combine 13 and y.

-3y2-2=y3-56

Subtract y3 from both sides of the equation.

-3y2-2-y3=-56

To write -3y2 as a fraction with a common denominator, multiply by 33.

-3y2⋅33-y3-2=-56

To write -y3 as a fraction with a common denominator, multiply by 22.

-3y2⋅33-y3⋅22-2=-56

Write each expression with a common denominator of 6, by multiplying each by an appropriate factor of 1.

Multiply 3y2 and 33.

-3y⋅32⋅3-y3⋅22-2=-56

Multiply 2 by 3.

-3y⋅36-y3⋅22-2=-56

Multiply y3 and 22.

-3y⋅36-y⋅23⋅2-2=-56

Multiply 3 by 2.

-3y⋅36-y⋅26-2=-56

-3y⋅36-y⋅26-2=-56

Combine the numerators over the common denominator.

-3y⋅3-y⋅26-2=-56

Simplify each term.

Simplify the numerator.

Factor y out of -3y⋅3-y⋅2.

Factor y out of -3y⋅3.

y(-3⋅3)-y⋅26-2=-56

Factor y out of -y⋅2.

y(-3⋅3)+y(-1⋅2)6-2=-56

Factor y out of y(-3⋅3)+y(-1⋅2).

y(-3⋅3-1⋅2)6-2=-56

y(-3⋅3-1⋅2)6-2=-56

Multiply -3 by 3.

y(-9-1⋅2)6-2=-56

Multiply -1 by 2.

y(-9-2)6-2=-56

Subtract 2 from -9.

y⋅-116-2=-56

y⋅-116-2=-56

Move -11 to the left of y.

-11⋅y6-2=-56

Move the negative in front of the fraction.

-11y6-2=-56

-11y6-2=-56

-11y6-2=-56

Add 2 to both sides of the equation.

-11y6=-56+2

To write 2 as a fraction with a common denominator, multiply by 66.

-11y6=-56+2⋅66

Combine 2 and 66.

-11y6=-56+2⋅66

Combine the numerators over the common denominator.

-11y6=-5+2⋅66

Simplify the numerator.

Multiply 2 by 6.

-11y6=-5+126

Add -5 and 12.

-11y6=76

-11y6=76

-11y6=76

Since the expression on each side of the equation has the same denominator, the numerators must be equal.

-11y=7

Divide each term in -11y=7 by -11.

-11y-11=7-11

Cancel the common factor of -11.

Cancel the common factor.

-11y-11=7-11

Divide y by 1.

y=7-11

y=7-11

Move the negative in front of the fraction.

y=-711

y=-711

The result can be shown in multiple forms.

Exact Form:

y=-711

Decimal Form:

y=-0.63‾

Solve for y -3/2y-2=1/3y-5/6